2013
DOI: 10.3390/agriculture3010012
|View full text |Cite
|
Sign up to set email alerts
|

Pyrolysis Kinetics of Physical Components of Wood and Wood-Polymers Using Isoconversion Method

Abstract: Two hardwood species, namely red oak and yellow-poplar, were separated into their bark, sapwood and heartwood components. The samples were tested for calorific value, specific gravity, proximate analysis, mineral composition, chemical composition, ultimate analysis, and thermo-chemical decomposition behavior. In addition, the thermo-chemical decomposition behaviors of cellulose, xylan, and lignin polymers were also tested. Thermo-chemical decomposition behavior was assessed using a thermo-gravimetric (TGA) sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
52
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(64 citation statements)
references
References 42 publications
11
52
1
Order By: Relevance
“…The second stage approximately started at 150 ºC and was completed at 400 ºC. At this major stage, the thermal degradation of the main component of biomass hemicellulose and cellulose can be identified as contributing to most loss of weight compared to other stages (Chen et al 2012;Jin et al 2013). The weight of untreated samples decreased from more than 90% to less than 40%.…”
Section: Thermal Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The second stage approximately started at 150 ºC and was completed at 400 ºC. At this major stage, the thermal degradation of the main component of biomass hemicellulose and cellulose can be identified as contributing to most loss of weight compared to other stages (Chen et al 2012;Jin et al 2013). The weight of untreated samples decreased from more than 90% to less than 40%.…”
Section: Thermal Propertiesmentioning
confidence: 99%
“…The difference in the weight in this stage might be attributed to there being a higher lignin content in untreated sample. It was reported that the lignin thermal degradation occurred at a low rate in the temperature range of 100 °C to 700 °C with a tiny peak at 340 °C (Jin et al 2013). The DTG curves (Fig.…”
Section: Thermal Propertiesmentioning
confidence: 99%
“…Constructed apparatus allows to study thermal decomposition of solid fuels and obtained thermogravimetric curves are similar to those that can be performed on commercial thermobalances [5][6][7][8][9]. The advantage of the device is definitely lower price than of commercial solutions (approx.…”
Section: Test Resultsmentioning
confidence: 70%
“…The weight loss observed at the first peak at 38 o C in DTG can be attributed to the moisture, while the two peaks observed at 260 and 350 o C are atrributed to hemicellulose and cellulose thermal degredation [43]. For liginin, no clear peaks were detected, though it might have been located at the same position as the cellullose peak, since lignin has tiny peak at 340ᵒC [44]. …”
Section: Thermal Characterisation Of Spbmentioning
confidence: 84%
“…There are three stages involved in the thermal decomposition of SPB: (1) the first stage at 25 to 125 o C, resulting in the loss of weight due to remove of bound and unbound water; (2) most loss in weight taking place in the second stage due to thermal degradation of the main component of biomass cellulose and hemicellulose at temperatures ranging from 150 to 400 o C [43,44]; and (3) slow weight loss in the third stage taking place at temperatures above 400 o C because of the sample's higher lignin content. Jin et al (2013) [44] reported that the thermal degradation of lignin occurred at a low rate in the range of 100 to 700ᵒC. This thermal degradation can be accompanied with a tiny peak at 340ᵒC.…”
Section: Thermal Characterisation Of Spbmentioning
confidence: 99%